EFFECT OF MACROPRUDENTIAL POLICY INSTRUMENTS ON CREDIT GROWTH FOR COMMERCIAL BANKS IN INDONESIA - Aslamah, Afidah Nur; Pratama, Aditya (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
The Indonesian economy experienced a deep contraction in 2020 due to the COVID-19 pandemic.The economic growth rate took a sharp dip at -5.32% in the first quarter based on data from BPS. One ofthe impacts is the decline in credit growth in the banking sector, which grew only 0.12% per August.The government is trying to control the rate of credit growth by introducing policies in the monetarysector, namely a change in the statutory reserve requirement (GWM) from 8% to 4% in order tomaintain banking liquidity. The purpose of this study was to analyze the effect of the statutoryreserve requirement, Macroprudential Intermediation Ratio (MIR), and capital buffer onthe growth of commercial bank credit in Indonesia 2019-2020. The data used is monthly data from theIndonesian Banking Statistics on the website of the Financial Services Authority. The statistical methodused in this study is the multiple linear regression method with E-Views SV.11 software to perform thethree hypothesis tests. The results of the study partially show that the reserve requirement has anegative and insignificant effect on commercial bank credit growth. MIR and capital buffer have asignificant effect, but MIR has a negative effect and capital buffer has a positive influence on commercialbank credit growth.